2022
DOI: 10.3389/fpubh.2022.936686
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of implementing a vial-sharing strategy for chemotherapy drugs using intelligent dispensing robots in a tertiary Chinese hospital in Sichuan

Abstract: IntroductionChemotherapy drug wasting is a huge problem in oncology that not only results in excessive expenses on chemotherapy drugs but also increases the cost of disposing of chemotherapy waste and the risk of occupational exposure in the environment. The main objective of this study was to evaluate the potential for hospitals in China to employ a real-time vial-sharing strategy that can save drug costs.MethodThis study was conducted retrospectively at Pharmacy Intravenous Admixture Services (PIVAS), People… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…In a recent study by Liu et al evaluating the potential for hospitals in China to employ a real-time vial-sharing strategy using a robot, this new technology was found to be of great help in saving up to ~59.08% of the total amount wasted of 24 different drugs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Liu et al evaluating the potential for hospitals in China to employ a real-time vial-sharing strategy using a robot, this new technology was found to be of great help in saving up to ~59.08% of the total amount wasted of 24 different drugs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Liu et al demonstrated decreased drug wastage of chemotherapeutic agents with intelligent dispensing robots and a vial-sharing strategy. 3 Sodre et al reported that when compared with standard single vial use, vial sharing for the intravitreal administration of bevacizumab resulted in a decrease in public health costs and increased the availability of the drug to public health care patients. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Various studies for other medications have shown a significant benefit with vial-splitting and drug repackaging, with decreased medication costs and less waste. 2 , 3 In these cases, the pharmacy performs vial splitting and repackaging under a sterile hood to ensure patient safety. It is important to note that vials should not be empirically split inside the operating room, as this can increase the risk of contamination between patients and violates the current standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…14 The emergence of the PIVAS has reduced the adverse reactions and patient mortality caused by contaminated and incorrectly mixed intravenous infusions and has improved work efficiency by guaranteeing clinically rational drug use and reducing the cost of drug allocation. 58…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The emergence of the PIVAS has reduced the adverse reactions and patient mortality caused by contaminated and incorrectly mixed intravenous infusions and has improved work efficiency by guaranteeing clinically rational drug use and reducing the cost of drug allocation. [5][6][7][8] The goal of the PIVAS is to centrally and precisely dispense finished infusions using standard operating procedures. 9 However, at present, the PIVAS's inability to reasonably use drugs is mainly focused on the review of prescriptions [10][11][12] despite the lack of standardized management of the process from configuration to delivery of medication to the patient, which results in the placement time for finished infusion solutions being overlooked.…”
Section: Introductionmentioning
confidence: 99%